Intention to adopt meat alternatives: Why gender-trait self-concept matters - Patrick Hartmann; Vanessa Apaolaza; Mario R. Paredes (Future Foods)
Understanding consumer attitudes towards meat alternatives is vital for reducing meat consumption and its negative environmental impacts. Drawing on social identity theory and recent research showing a link between dietary choices and gender norms, this study examines the relationship between gender-traits self-concept—self-perceived feminine and masculine traits—and consumer’s intention to adopt plant-based meat alternatives, moving beyond traditional analyses of gender influences. Our survey data collected 2023 from a representative U.S. sample (18+, N=800) showed that binary gender did not relate significantly to the intentions to buy meat plant-based meat alternatives. Instead, a more feminine gender-trait self-concept was positively associated with meat-alternative adoption intention. However, a more detailed analysis showed that this association was only significant for men, whereas, among women, self-perceived masculinity increased the intention to adopt meat alternatives. These findings suggest that individuals who adopt traits less commonly associated with their gender may be more open to dietary shifts, challenging assumptions that women are more inclined toward meat alternatives. By highlighting the interplay between gender-trait self-concept and the intention to adopt meat alternatives, this research contributes to a more nuanced understanding of dietary behavior. The findings imply that marketing strategies and public health campaigns should address a broader spectrum of gender traits to effectively promote sustainable dietary choices.